Aerodynamic energy consumption analysis of divided evacuated tube transportation system - Ziwei Zhang; Yingxue Wang; Guanqing Wang; Feilong Li; Dengke Wang; Jianjun Luo (Engineering Applications of Computational Fluid Mechanics)
Evacuated Tube Transportation (ETT) reduces aerodynamic drag and energy consumption by lowering gas pressure around high-speed trains (HSTs). To optimise this effect, integrating the ETT system into high-speed cruise segments is a practical approach, though it may introduce vacuum potential energy losses. To address this, the paper put forward a Divided Evacuated Tube Transportation (D-ETT) system to seamlessly connect open-line and tube operation of HST then the regulations of aerodynamic energy consumption were studied. Theoretical discussions into reasonable parameter range including tube design and HST operation manners were conducted and then formed system-designing strategy. The spatial and temporal distribution law of tube gas circumstances were examined through model testing and numerical simulation. Three-dimensional, unsteady and compressible fluid models were established using Large Eddy Simulation (LES) to analyse tube fluid characteristics. Relative results indicated that under reasonable D-ETT designing strategies with larger blockage ratios, higher HST speeds, larger total mileage and mileage ratio of the mid-section, the aerodynamic energy saving effect is more impressive. The mixing of the adjacent tube gases with differential pressure induced gas-mixing fluctuations then changed the fluid circumstances inside the tube. The positional relationship between HST and gas waves infected aerodynamic energy consumption. By figuring out the spatiotemporal variation of tube gas, the theoretical energy estimation scheme for aerodynamic energy consumption with various cases was put forward, then the rationality and accuracy of which was verified by numerical simulation with prediction error less than 8%. The saving ratio of aerodynamic drag energy consumption of a 10 km tube could be 39.9% compared to traditional tunnels, which will be higher under ultra-long mileage, thus realising the overall aerodynamic energy saving effect. High-amplitude pressure waves intensified the pressure changes around HSTs, making it necessary to use HST capsules with superior sealing performance to ensure eardrum comfort.